PENINGKATAN PENGETAHUAN, SIKAP, DAN KETERAMPILAN IBU-IBU PKK DESA MAKAMHAJI MENGENAI PENANGGULANGAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Arif Widodo (Universitas Muhammadiyah Surakarta, 2007)
Blood Fever Dengue is one of the contagious diseases which maycause death. The existence of the endemic area is one indicator of thefailure in fighting against such disease. One of the main efforts whichhas high level of success is the efforts to eliminate the mosquito nest.Every year in Makam Haji Kartasura, it often appears some victims ofsuch disease. The illumination about the eliminating of the mosquitonest to prevent the spread of Blood Fever Dengue in the Hall of MakamHaji shows a significant result. The “PKK” participants who previouslyhave no idea about the cause, contamination, and the elimination ofmosquito nest turn to have full knowledge about it. After having fullunderstanding about it, they become aware of the way how to avoid andcombat these Aides Aegepty mosquitoes. This illumination program isalong with the model of applied prevention of such disease like the correctway to clean the bath tub, the way to have healthy household condition,the burial of second hands which may result water filling it, and how tocare for the victims of such disease.